Investigation of the effect of passive therapy and active exercise therapy in athletes suspected of low back pain with Piriformis muscle contracture - Hashimoto, H.; Shibahara, M.; Osaki, M. (Journal of Physical Education and Sport, 2023)
Problem statement Recently, a relationship between piriformis syndrome and nonspecific low back pain has been proposed; however, this has only been investigated in terms of the patient's subjective pain and anatomical and structural perspectives. Furthermore, it has been suggested that evaluating changes in the piriformis muscle elastic modulus is a painless and noninvasive method for the measurement of changes in nonspecific low back pain after passive therapy; however, this was only evaluated cross-sectionally and did not clarify the long-term changes caused by continuous passive therapy intervention.